The single-cell spatial landscape of stage III colorectal cancers - Andrew Su; HoJoon Lee; Minh Tran; Richard C. dela Cruz; Anuja Sathe; Xiangqi Bai; Ignacio Wichmann; Lance Pflieger; Bryce Moulton; Tyler Barker; Derrick Haslem; David Jones; et al. (npj Precision Oncology)
Abstract We conducted a spatial analysis of stage III colorectal adenocarcinomas using Hyperion Imaging Mass Cytometry, examining 52 tumors to assess the tumor microenvironment at the single-cell level. This approach identified 10 distinct cell phenotypes in the tumor microenvironment, including stromal and immune cells, with a subset showing a proliferative phenotype. By focusing on spatial neighborhood interactions and tissue niches, particularly regions with tumor-infiltrating lymphocytes, we investigated how cellular organization relates to clinicopathological and molecular features such as microsatellite instability (MSI) and recurrence. We determined that microsatellite stable (MSS) colorectal cancers had an increased risk of recurrence if they had the following features: 1) a low level of stromal tumor-infiltrating lymphocytes, and 2) low interactions between CD4 + T cells and stromal cells. Our results point to the utility of spatial single-cell interaction analysis in defining novel features of the tumor immune microenvironments and providing useful clinical cell-related spatial biomarkers.